The Spanish Labor Universities and the Belgian Labor University: An Example of Education Transfer and Transformation (1955–1983) - Sanchidrián Blanco, Carmen; Molina Poveda, María (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2020)
The Falange of José Antonio Primo de Rivera and the Franco regime imported from other countries several institutions, among them, the Labour Universities (1955-1983). José Antonio Girón was the founder, although to create them he followed the Belgian Labor University (1911) created by Paul Pastur. In this paper, we will analyze the similarities and differences between both institutions through the information that NO-DO (Noticiarios-Documentales) (Newsreels and Documentaries, audiovisual propaganda of Franco’s regime) offered in its newsreels about the Spanish Labour Universities. Both institutions were similar in the architecture, in the design of spaces, and in offering different specialties, mainly in the industrial field. They differed in the context in which they were born. The Belgian Labor University was also imported into other countries such as France, Zaire, Montevideo, Iran and China.